PENGARUH ALIRAN DUA FASA GAS-CAIR TERHADAP FLUKTUASI GAYA PADA DINDING PIPA HORIZONTAL - Irsyad, Muhammad (Jurnal MEKANIKAL, 2012)
One of the causes damage to the pipeline is vibration caused by fluctuation in the flow. Two-phase flow of liquid - gas at high pressure will provide a fluctuating impact load. Fluctuations in stream flow patterns are shown by the form. It is necessary to note the fluctuation force on a straight pipe wall in accordance with the flow pattern is formed. This study uses two-phase flow by varying the flow of air and water. Variations of water flow are 5,10,15, 20, 25, 30 and 35 lpm. While the variations of air flow used are 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 lpm. The sensor used a strain gauge type GFCA 3-50 to read the strain in the pipe. The results indicate that the greatest force at the time of the bubble flow patternÂ  is 0.143 N and its value is relatively stable. While the slug flow pattern shows the force generated more fluctuations than the other flow patterns.